2013
DOI: 10.1080/19393210.2013.764551
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxins in black tea in Iran

Abstract: Aflatoxins (AFs) are highly toxic, and carcinogenic secondary fungal metabolites and have been detected in various food commodities. In this regard, 40 black tea samples including domestic and imported black tea were analysed for aflatoxin contamination by high-performance liquid chromatography using a post-column derivatisation procedure (Kobra cell) with fluorescence detection. Samples were randomly collected in 2010 from Tehran markets. The results revealed that 30 among 40 samples were contaminated with af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 2 publications
1
16
0
Order By: Relevance
“…However, only a few reports are available regarding the levels of aflatoxins in black tea. Pouretedal and Mazaheri (2013) analyzed the concentration of aflatoxins in 40 samples of raw black tea collected from Iranian markets and found 27.5% (n = 30) samples positive for aflatoxins, while the mean concentrations of AFB 1 and TAF were 10 and 12.07 µg/kg, respectively. In China, the mean concentration of AFB 1 in the samples of raw pu-erh tea and ripe pu-erh tea was 8.33 and 20.149 µg/kg, respectively (Li et al, 2015).…”
Section: Occurrence Of Aflatoxins In Non-branded and Branded Teamentioning
confidence: 99%
See 1 more Smart Citation
“…However, only a few reports are available regarding the levels of aflatoxins in black tea. Pouretedal and Mazaheri (2013) analyzed the concentration of aflatoxins in 40 samples of raw black tea collected from Iranian markets and found 27.5% (n = 30) samples positive for aflatoxins, while the mean concentrations of AFB 1 and TAF were 10 and 12.07 µg/kg, respectively. In China, the mean concentration of AFB 1 in the samples of raw pu-erh tea and ripe pu-erh tea was 8.33 and 20.149 µg/kg, respectively (Li et al, 2015).…”
Section: Occurrence Of Aflatoxins In Non-branded and Branded Teamentioning
confidence: 99%
“…Moreover, black tea is also reported to contain appreciable quantities of some essential micronutrients such as fluoride, copper, and manganese (Zhang et al, 2018b). However, despite being a source of several health-promoting components, tea samples are also reported to be contaminated by a number of toxicants, the most critical among which are the mycotoxins, especially aflatoxins (Viswanath et al, 2012;Pouretedal and Mazaheri, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Aflatoxins, ochratoxin A, and fumonisins were found in black tea samples. Aflatoxin B1 mean concentration achieved 10 µg/kg [ 30 ]. The extremely high concentration of ochratoxin A was found in black tea from the Czech Republic—up to 250 µg/kg [ 39 ].…”
Section: Mycotoxins In Teamentioning
confidence: 99%
“…The presence of toxigenic microfungi in black tea represents a risk of contamination by mycotoxins, e.g. ochratoxin A (OTA), fumonisin B 1 , fumonisin B 2 , fumonisin B 4 and aflatoxins . It has been shown that 7% of Aspergillus niger isolates from herbal teas are able to produce OTA .…”
Section: Introductionmentioning
confidence: 99%